Mammalian RNAi: a practical guide. (August 2005) - Sandy, Peter; Ventura, Andrea; Jacks, Tyler
Silencing of gene expression by RNA interference (RNAi) has become a powerful tool for the functional annotation of the Cae-norhabditis elegans and Drosophila melanogaster genomes. Recent advances in the design and delivery of targeting molecules now permit efficient and highly specific gene silencing in mammalian systems as well. RNAi offers a simple, fast, and cost-effective alternative to existing gene targeting technologies both in cell-based and in vivo settings. Synthetic small interfering RNA (siRNA) and retroviral short hairpin RNA (shRNA) libraries targeting thousands of human and mouse genes are publicly available for high-throughput genetic screens, and knockdown animals can be rapidly generated by lentivirus-mediated transgenesis. RNAi also holds great promise as a novel therapeutic approach. This review provides insight into the current gene silencing techniques in mammalian systems.